Makna Baptisan Air, Roh Kudus, dan Api: Refleksi Teologis Berdasarkan Matius 3:11 untuk Kehidupan Orang Percaya - Faduhu O Ndruru; Sugiono Sugiono (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2025)
This study aims to analyze the theological meaning of water baptism, the baptism of the Holy Spirit, and the baptism of fire, focusing on the understanding contained in the Gospel of Matthew 3:11. Through a hermeneutic approach, systematic theology, and contextual analysis, this study examines the relationship between the three types of baptism in the context of salvation and the journey of faith of believers. Matthew 3:11, which contains John the Baptist's statement about the baptism of water, the Holy Spirit, and fire, is the starting point in exploring the meaning of each baptism, both historically, culturally, and theologically. The results of the study show that water baptism leads to repentance and renewal of life, the baptism of the Holy Spirit strengthens faith and empowers believers, while the baptism of fire functions as a purification and test of faith. This study also found that the three baptisms complement each other in shaping the spiritual life of Christians, and have relevant applications in contemporary church life. This study offers novelty by analyzing the theological meaning of water baptism, the baptism of the Holy Spirit, and the baptism of fire in Matthew 3:11 through a hermeneutic and systematic theology approach. The study highlights the interconnection of these three baptisms as complementary elements in shaping the spiritual life of Christians, as well as their relevance in the context of contemporary churches.